Modern Art in Pakistan - Wille, Simone, author.
1 online resource (144 pages).
Keywords: Modern Art in Pakistan examines interaction of space, tradition, and history to analyse artistic production in Pakistan from the 1950s to recent times. It traces the evolution of modernism in Pakistan and frames it in a global context in the aftermath of Partition. A masterful insight into South Asian art, this book will interest researchers, scholars, and students of South Asian art and art history, and Pakistan in particular. Further, it will be useful to those engaged in the fields of Islamic studies, museum studies, and modern South Asian history.